Thiamine status of feedlot cattle fed a high-concentrate diet - Karapinar, Tolga; Dabak, Murat; Kizil, Omer (Canadian Vet Med Assoc, 2010)
As thiamine status of ruminants is adversely affected by rumen acidity, this study investigated whether or not thiamine deficiency occurs in feedlot cattle fed a high concentrate diet. Fifty 1- to 2-year-old feedlot cattle fed a high concentrate diet (75% barley) for at least 3 mo (high concentrate diet group) and 15 healthy feedlot cattle of similar ages (control group) that were fed a low concentrate diet (30% barley) were used. Rumen fluid samples were obtained by rumenocentesis and their pH was determined with a portable pH meter. Blood samples taken from all animals from a jugular vein were used to determine erythrocyte transketolase enzyme activity, and hence thiamine pyrophosphate (TPP) effect. Odor and mean pH values of ruminal fluid samples from the high concentrate diet and control group were acidic (pH 5.3) and aromatic (pH 6.1), respectively. The mean TPP effect % in the high concentrate diet group (47.2 +/- 3.2) was significantly higher than in the control group (19.53 +/- 2.5) (P < 0.001). The study provides evidence of a TPP effect in feedlot cattle fed a high concentrate diet.
Keywords: Lactic-Acidosis; Dairy-Cows; Sheep; Polioencephalomalacia; Deficiency